2005
DOI: 10.1007/s00774-005-0621-8
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a low sodium diet on bone metabolism

Abstract: Osteoporosis is a serious public health problem, and dietary interventions may potentially be helpful in preventing this disorder. The purpose of this study was to determine the effects of a low sodium diet on bone metabolism in postmenopausal women. This was a longitudinal study to determine the effects of a low sodium (2-g/day) diet on bone. Forty postmenopausal African-American and Caucasian women were enrolled in a 2-g/day sodium diet for 6 months. Sodium and calcium excretion, bone turnover, and calcitrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0
1

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 47 publications
0
15
0
1
Order By: Relevance
“…A reabsorção renal de Ca é diretamente proporcional à reabsorção de sódio (Na) e, ao elevar-se o NaCl, a reabsorção fracional de Na é diminuída, ocasionando redução paralela na absorção de Ca e prejuízos à MO (44) . Carbone et al sugeriram que, em mulheres na pós-menopausa, dieta restrita em Na (2g/dia) poderá ser benéfica para a DMO (44) .…”
Section: Papel Dos Minerais Na Saúde óSseaunclassified
“…A reabsorção renal de Ca é diretamente proporcional à reabsorção de sódio (Na) e, ao elevar-se o NaCl, a reabsorção fracional de Na é diminuída, ocasionando redução paralela na absorção de Ca e prejuízos à MO (44) . Carbone et al sugeriram que, em mulheres na pós-menopausa, dieta restrita em Na (2g/dia) poderá ser benéfica para a DMO (44) .…”
Section: Papel Dos Minerais Na Saúde óSseaunclassified
“…14 Laura et al also report that serum propeptide of type I collagen, a bone formation marker, is significantly decreased with a low-sodium diet. 15 Because the effect of excessive sodium intake on bone turnover has not been well established, we aimed to assess changes of bone turnover markers according to the amount of urinary sodium excretion, which is closely associated with dietary sodium intake in Korean postmenopausal women with low bone mass.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, between sodium intake and BMD of the ultradistal radius and hip in male and female participants of the Rancho Bernardo study (an on-going Californian study started in 1972 examining life style and nutritional parameters in relation to various health outcomes in several thousand adults), although, after adjusting for confounders, the statistical significance disappeared in women, but remained in men at the ultradistal radius. The results from numerous other studies did not show any direct relationship between Na intake/urinary excretion and BMD as an outcome, but did show higher urinary Ca excretion with higher urinary Na (Carbone et al 2005;Dawson-Hughes et al 1996;Matkovic et al 1995).…”
Section: Introductionmentioning
confidence: 65%
“…The above studies might have been too acute or too short to simulate free-living conditions or to allow for normal physiological adaptation. Carbone et al (2005) reported the results from a 6-month intervention with low-Na diet (2 g/day) in 40 postmenopausal Caucasian and African-American women. They found decreased activity of a bone formation marker, aminoterminal propeptide of type I collagen, in subjects Fig.…”
Section: Discussionmentioning
confidence: 98%